The cultural landscape affection: life intimacy - Ismail, Nor Atiah; Mohd Tahir, Osman; Sujak, Siti Syahirah (Universiti Putra Malaysia Press, 2014)
Culture plays an important role in our lives and shapes our experience. The role of culture in influencing landscape experience is obvious.